Improving the Mechanical Properties of Single-Walled Carbon Nanotube Sheets by Intercalation of Polymeric Adhesives - COLEMAN, JONATHAN; BLAU, WERNER (My University, 2003)
Organic polymers, such as poly(vinyl alcohol), poly(vinyl pyrrolidone), and poly(styrene), were intercalated into single-walled carbon nanotube sheets by soaking the sheets in polymer solutions. Even for short soak times, significant polymer intercalation into existing free volume was observed. Tensile tests on intercalated sheets showed that the Young?s modulus, strength, and toughness increased by factors of 3, 9, and 28, respectively, indicating that the intercalated polymer enhances load transmission between nanotubes.
PUBLISHED
Keywords: Physics; load transmission